2019
DOI: 10.4103/jfmpc.jfmpc_391_18
|View full text |Cite
|
Sign up to set email alerts
|

Designing culturally acceptable screening for breast cancer through artificial intelligence-two case studies

Abstract: Diffusion of Innovation (DOI) theory explains how, over a period of time, an idea or behavior diffuses (or spreads) through a targeted population or society. The major thing about adoption is that the people must perceive the idea, behavior, or product as new or innovative and it should be useful to them. The more the perceived benefit, the quicker is the diffusion. Same thing can be expected for adoption of new technology in healthcare also. In this paper, we have described two novel breast cancer screening t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…10 Broach et al reported a sensitivity of 86 % and specificity of 89% with iBE. 9 So far, the most widely used tools globally for breast cancer examination are Mammography, clinical breast examination (CBE), and breast self-examination (BSE). 20 Mammography and regular CBE are known to reduce fatality through early detection of breast cancer even in asymptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Broach et al reported a sensitivity of 86 % and specificity of 89% with iBE. 9 So far, the most widely used tools globally for breast cancer examination are Mammography, clinical breast examination (CBE), and breast self-examination (BSE). 20 Mammography and regular CBE are known to reduce fatality through early detection of breast cancer even in asymptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The device is radiation-free, which can also be operated by grass-root health workers with minimal training. 9 It contains lead zirconate titanate piezoelectric cantilever sensor which precisely detects atypical, abnormal parts of the breast by comparison of the degree of deflection. 10 This could be a potential powerful screening tool in resource-poor and highly populated nations like India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, cultural appropriateness is an indispensable quality of effective health care message delivery. In a country such as India, which is highly diverse, a deeper understanding of the rural community is important for effective public health message delivery [17].…”
Section: Use Of Symbols In Health Care and Disease Managementmentioning
confidence: 99%
“…Broad cycle and regular use of HIT will improve health-care quality; reduce medical flaws; decrease the cost of health care; decline paperwork; improve administrative efficiencies; and broaden access to economical care. [ 1 2 3 4 5 6 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%